2022
DOI: 10.29244/jintp.20.3.123-129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Kebutuhan Nutrien dan Suplementasi Zinc untuk Calon Galur Ayam IPB-D2 Fase Pre-layer

Abstract: This study aimed to evaluate nutrient requirements and zinc supplementation for IPB D-2 pre-layer chicken line candidates on performance, blood profile, and blood malondialdehyde (MDA). This study used 200 of 16 weeks IPB-D2 chickens line candidates reared until 19 weeks of age (pre-layer phase). This study used a completely randomized design (CRD) with 2 treatments and 10 replications. The treatment rations were formulated to fill the chicken nutrient requirements according to Lohman (2020) without the additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
1
1
Order By: Relevance
“…This is in accordance with (Fahrina et al, 2021) nutrient contents on the increase in basophils (Salsabila et al, 2022). The values of lymphocytes and basophils in this study compared with those in (Falah et al, 2022) are still within the normal range and lower than the basophil value reported by (Salsabila et al, 2022), which is 1.91%-2.02%. A low value of lymphocytes and basophils indicates that the chicken is in a healthy condition, while a high value indicates that the chicken is in an unhealthy condition.…”
Section: Effect Of Treatment On the Blood Profile Of 12-week-old Ipb-...supporting
confidence: 92%
See 2 more Smart Citations
“…This is in accordance with (Fahrina et al, 2021) nutrient contents on the increase in basophils (Salsabila et al, 2022). The values of lymphocytes and basophils in this study compared with those in (Falah et al, 2022) are still within the normal range and lower than the basophil value reported by (Salsabila et al, 2022), which is 1.91%-2.02%. A low value of lymphocytes and basophils indicates that the chicken is in a healthy condition, while a high value indicates that the chicken is in an unhealthy condition.…”
Section: Effect Of Treatment On the Blood Profile Of 12-week-old Ipb-...supporting
confidence: 92%
“…Temperature and environmental factors can affect leukocyte differentiation. The differentiation values of other leukocytes, such as heterophils, eusinophils and monocytes, are still within the normal range according to the standard of (Falah et al, 2022) but the research of (Salsabila et al, 2022) on heterophils and monocytes of 12week-old IPB-D3 chickens had lower values than this study. Heterophils and monocytes are important components of the immune system that work quickly to kill pathogens and direct signals to the body's immune response mechanism, which indicates that the immune system of IPB-D3 chicken candidate strains is more advanced.…”
Section: Effect Of Treatment On the Blood Profile Of 12-week-old Ipb-...contrasting
confidence: 67%
See 1 more Smart Citation
“…This is because chickens with high slaughter weight in the grower phase will have a lower potential for decreased egg production and high mortality in the layer phase. This statement is [31] that excess weight growth during growth negatively correlates with egg production performance.…”
Section: Percentage Of Non-carcass Weight Of Ipb-d2 G4 and Ipb-d3 G2 ...mentioning
confidence: 91%